Sete anos após a introdução da vacina pneumocócica 10 valente no Programa Nacional de Imunizações no Brasil : impacto direto e indireto - Varela, Fernanda Hammes (2019)
Introduction: Streptococcus pneumoniae is the main etiological agent of bacterial pneumonia, and a major cause of death, especially in children and the elderly. Brazil introduced the PHiD-CV in 2010. Methods: Ecological study of all ages collected from a National open-access database (DATASUS), being the period studied between 2002 and 2017. A descriptive analysis of the pre versus post-vaccinal period was made. For the time series analysis, R software was used. Objectives: Seven years after introduction in National Immunization Program, the aim was to evaluate the direct and indirect impact of PhiD-CV for three pneumonia outcomes were analyzed: hospitalization, mortality, and length of stay (LOS). Results: There was a significant reduction in the incidence of hospital admission in all age groups, except in adolescents between 10 to 19 years. There was a decrease in hospitalizations due to pneumonia with monthly reduction trend of -9.6 (-15.4, -3.7 – 95% CI; p=0.0016) and -2.2 (-4.6, -0.1 – 95% CI; p=0.044) for those <1 year and >80 years, respectively. Mortality was significantly lower in the post-vaccination period for all age groups over 5 years. LOS significantly increased for all age groups younger than 80 years. Conclusion: The PHiD-CV in Brazilian National Immunization Program reduced hospitalizations and deaths due to pneumonia in the vaccinated and non-vaccinated inhabitants in a sustained and progressive manner. This study supports a herd effect in the elderly seven years after the introduction of a pneumococcal vaccine. The sustained impact of PHiD-CV should be consistently reassessed both by the risk of replacement of the pneumococcal serotypes and by the change in the vaccination schedule, 2+1 since 2016.